2011
DOI: 10.1093/annonc/mdr019
|View full text |Cite
|
Sign up to set email alerts
|

The role of relatives in decisions concerning life-prolonging treatment in patients with end-stage malignant disorders: informants, advocates or surrogate decision-makers?

Abstract: If relatives are to play an important part in EOL decision making, we must devise strategies to recognise their potential as patients' advocates as well as their own needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 28 publications
1
38
0
6
Order By: Relevance
“…Effective communication skills can be improved with training and transferred into a clinical setting having an enduring impact 18; 19. Also, in this survey there appears to be a mismatch between the 50% of Italian oncologists that are ready to thoroughly inform the patient on the prognosis and 90% that are prepared to talk about this issue with the family - this is clearly a different handling than in other countries 20. This could reflect a cultural background, as well as a lack of training in communication skills that is strongly advocated by most medical oncologists.…”
Section: Discussionmentioning
confidence: 81%
“…Effective communication skills can be improved with training and transferred into a clinical setting having an enduring impact 18; 19. Also, in this survey there appears to be a mismatch between the 50% of Italian oncologists that are ready to thoroughly inform the patient on the prognosis and 90% that are prepared to talk about this issue with the family - this is clearly a different handling than in other countries 20. This could reflect a cultural background, as well as a lack of training in communication skills that is strongly advocated by most medical oncologists.…”
Section: Discussionmentioning
confidence: 81%
“…In das Erkrankungsgeschehen sind Angehörige sowohl als Unterstützer, Pflegende und/oder als Mitbetroffene einzubeziehen [9,10]. Am Therapieentscheidungsprozess partizipieren Angehörige zumeist implizit, aber auch explizit, z.…”
Section: Therapiezielfindung Und Kriterien Der Entscheidungsfindungunclassified
“…A qualitative interview study with 38 patients with advanced cancer and their oncologists (n = 21) found that patients and oncologists shared similar views about family involvement in such decisions, highlighting the importance for patients' understanding of their disease and family emotional support [42] . However, clinical evidence demonstrates that oncologists are still reluctant to involve family or else involve them too late in the course of the disease [43][44][45] .…”
Section: Patients' Preferences Regarding Family Involvement In Decisimentioning
confidence: 99%